Análise de anomalias térmicas em função da geometria urbana em Cuiabá-MT - Souza, Natallia Sanches e (2019)
Thermal anomalies are changes in air temperature, especially in urban areas, where the effects of urbanization and environmental degradation compromise the quality of life and comfort of the population in cities. The modification of the natural environment to an urban environment results in thermal anomaly phenomena of urban heating, called urban heat island, which characterizes a higher air temperature in urban areas, when compared to less urbanized neighboring regions.In order to produce an environmentally balanced urban environment that is adequate to human needs it is necessary to consider a close relationship between the urban environment and the microclimate. The climate of Cuiabá is Aw in the Koppen classification with high temperatures, rain in summer and dry in winter. That said, this research aimed to analyze thermal anomalies as a function of urban geometry configuration in three urban portions of Cuiabá-MT. For that they were conducted qualitative and quantitative analyzes of land cover and micro-climatic variables (air temperature, relative humidity and wind direction) obtained by three micrometeorological stations. Based on the results presented, the land cover was a determining factor in the significant differences found between the microclimatic variables of urban areas. In addition, anthropogenic changes and the urban density affected air temperature and relative humidity, as well as the incidence and magnitude of urban heat island. The highest air temperatures occurred during the day, during the hours of greatest solar radiation incidence, the relative humidity was inversely the air temperature and the wind direction was the monsoon regime in the north-east range in the wet and southwest-south periods in the hot-dry period. The thermal anomaly presented incidence of urban heat island and cool island. In general, the highest amplitudes were found in the hot-dry period. Therefore, this study was adequate to analyze the relationship of microclimatic variables and ground cover, indicating the incidence and magnitude of thermal anomalies. It can then demonstrate the importance of land cover analysis in urban planning in order to mitigate the climate rigor imposed by the climate of still developing cities such as Cuiabá.